(3eONd eYGUQ aj fXe GdeYdheGJ GdeMGSHjIs - (3ceGd GdOjf eUWai(B, (3GdOgQGhjs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2003)
(3GdeaGgje GdGSGSjI dfXe GdeYdheGJ(B- (3JTZjd GdeYdheGJ aj fXGe GdeYdheGJ GdeMGSHj(B- (3OhQI GdYedjGJ(B- (3JMdjd fXe GdeYdheGJs
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s